Suriname. Significant achievements 2011 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
The main activities carried out by the Institute in Suriname during 2011 are identified, with respect to the needs and interests of the country, strengthening topics such as organic agriculture, greenhouses, protected agriculture, technology, livestock, conservation, agrotourism, animal husbandry and production. of seeds, chili and vegetables.